2020
DOI: 10.3389/fneur.2020.574036
|View full text |Cite
|
Sign up to set email alerts
|

Association Between Plasma Lipoprotein-Associated Phospholipase A2 and Plaque Vulnerability in TIA Patients With Unilateral Middle Cerebral Artery Stenosis

Abstract: Background: Plasma lipoprotein-associated phospholipase A2 (Lp-PLA2) has emerged as a novel biomarker for coronary atherosclerosis. However, the association between Lp-PLA2 and plaque vulnerability in atherosclerosis of cervicocerebral arteries remains poorly defined, especially for intracranial atherosclerotic stenosis (ICAS). We aimed to investigate the association between Lp-PLA2 and plaque vulnerability in transient ischemic attack (TIA) patients with unilateral middle cerebral artery stenoses (MCAs). Meth… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 41 publications
0
3
0
Order By: Relevance
“…As a high-risk factor for atherosclerotic vascular disease and cardiovascular disease, Lp-PLA2 has received more and more attention. Recent studies have found that the level of Lp-PLA2 is not only related to the formation of lipid atherosclerotic plaques, ischemic stroke and vascular inflammation, but also to the occurrence of coronary heart disease (Bonnefont-Rousselot, 2016;Qiao et al, 2020;Qin et al, 2020). Lipid metabolism plays an important regulatory role in the occurrence and development of cardiovascular and cerebrovascular diseases (Esenwa and Elkind, 2016;Zhang et al, 2020).…”
Section: Introductionmentioning
confidence: 99%
“…As a high-risk factor for atherosclerotic vascular disease and cardiovascular disease, Lp-PLA2 has received more and more attention. Recent studies have found that the level of Lp-PLA2 is not only related to the formation of lipid atherosclerotic plaques, ischemic stroke and vascular inflammation, but also to the occurrence of coronary heart disease (Bonnefont-Rousselot, 2016;Qiao et al, 2020;Qin et al, 2020). Lipid metabolism plays an important regulatory role in the occurrence and development of cardiovascular and cerebrovascular diseases (Esenwa and Elkind, 2016;Zhang et al, 2020).…”
Section: Introductionmentioning
confidence: 99%
“…Lp-PLA2 levels might be a useful tool to identify patients with ICAS at higher risk of new vascular events (31). For TIA patients with unilateral middle cerebral artery stenoses, Lp-PLA2 levels may also be a promising biomarker to predict plaque vulnerability (32). However, there are few studies on the association of Lp-PLA2 with stenosis subtype in patients with AIS.…”
Section: Discussionmentioning
confidence: 99%
“…Lipoprotein-associated phospholipase A2 (Lp-PLA2) is a novel calcium-independent lipolysis enzyme, also known as platelet activator acetylhydrolase, which binds to circulating low density lipoprotein cholesterol and promotes the initiation of atherosclerosis. As a new marker of the vascular inflammatory response, it plays an important role in the formation and development of plaque ( Zhang, Lu & Zhang, 2018 ), and can affect the stability of atherosclerotic plaque, promote plaque rupture, and ultimately lead to acute cerebrovascular events ( Bonnefont-Rousselot, 2016 ; Qin et al, 2020 ).…”
Section: Introductionmentioning
confidence: 99%